Kembalinya Barata Kulisusu: Kebangkitan Identitas Kelompok Bangsawan Kulisusu Dalam Proses Pemekaran Kabupaten Buton Utara - Nurlin Nurlin (Hasanuddin University, 2016)
Abstract The expansion of a new autonomous region (DOB) not only provides an arena for reproductive power of local elites, such as politicians, senior bureaucrats and businessmen, but also provides an access for the adatleaders to reaffirm the symbol of power attached to their heritable nobility. This article aims to explain the process of reproductive powers of Kulisusu aristocratic in the expansion process of North Buton regency. The reproduction of identity and power of Kalisusu royalty in the expansion process of North Buton begun since adat leaders got involved in the expansion of political activities in order to legitimize the emergence of North Buton identity. To legitimize North Buton identity, adat leaders are supported by the claims that they have genealogical relationship with their ancestors, the founders of Kalisusu royal nobility. The involvement of adat leaders is, in fact, not on their own initiative, but by the expansion agents. However, the involvment of adat leaders have precisely giventhem a space for reproductive power in a new autonomous regions, North Buton. It shows how the reproduction of identity is closely associated with theirfuture interests. The study also found that the return of the rule of Kulisusu aristocratic into a new contestation isaimed to find the foundation of original Kalisusu adat.